Magnetic resonance elastography and transient elastography as non‐invasive analyses for liver fibrosis: can they obviate the need for liver biopsy in psoriasis patients treated with methotrexate?. (July 2015) - Kaffenberger, Benjamin H.; Kaffenberger, Jessica A.; Wong, Henry; Jarjour, Wael; Levin, Douglas; Bechtel, Mark A.
Abstract The liver biopsy has been regarded as the reference standard method of monitoring hepatic fibrosis in psoriasis patients treated with methotrexate. It has also been subject to concerns over sampling error, internal and external variability, and potential for morbidity and mortality. During the past two decades, two imaging techniques, magnetic resonance elastography and transient elastography, have been developed and approved by the US Food and Drug Administration (FDA) for the assessment of hepatic fibrosis. Although high‐quality, psoriasis‐specific data are lacking, both methods have been shown to have outstanding efficacy in the detection of hepatic fibrosis, particularly the more advanced stages which may warrant the choice of a therapeutic alternative to methotrexate. Dermatologists should be aware of the availability of these tests and understand their limitations. Prospective studies in psoriasis and methotrexate management using these techniques are needed.